PERBANDINGAN KARAKTERISTIK PAPAN SEMEN DARI BATANG DAN CABANG KAYU ASAL HUTAN RAKYAT - . Suhasman (PERENNIAL, 2012)
Optimum utilization of raw materials is very important to overcome the limited raw materials supply. The objective of this study was to analyze the physical and mechanical properties of cement board made of stem and branch of tree. Materials used in this study were three wood species from community forest, namely; sengon (Paraserianthes falcataria), candlenut (Aleurites moluccana), and gmelina (Gmelina arborea). The raw materials taken from stem and branch of tree were converted into particle using hammer mill. Composition of particle, water, and cement weight based were 1 : 1,25 : 2,5 for produce cement board, while density target of the boards were 0.85 g cm-3. To improve the board quality, 2.5 % CaCl2 based on cement weight was added. Mixed meterials then cold pressed during 24 hours and then conditioned for 1 month before tested. The research resuts are as follows: 1) Dimensional stability of cement board made from stem were superior compared to cement board made from branch of tree, 2) The MOR and Internal Bond of cement board have no clear different pattern between stem and branch of tree, 3) The MOE of cement board made from branch were higher compared to cement board made from stem of the three wood species. Key words: Cement board, community forest, sengon, candlenut, gmelina